Huang Lian Jie Du decoction attenuated colitis via suppressing the macrophage Csf1r/Src pathway and modulating gut microbiota - Su, Shan; Liu, Ting; Zheng, Jia-Yi; Wu, Hai-Cui; Keng, Vincent W.; Zhang, Shi-Jie; Li, Xiao-Xiao (Frontiers in Immunology, 2024)
Introduction Ulcerative colitis, a subtype of chronic inflammatory bowel disease (IBD), is characterized by relapsing colonic inflammation and ulcers. The traditional Chinese herbal formulation Huang Lian Jie Du (HLJD) decoction is used clinically to treat diarrhea and colitis. However, the mechanisms associated with the effects of treatment remain unclear. This study aims to elucidate the molecular mechanistic effects of HLJD formulation on colitis. Methods Chronic colitis in mice was induced by adding 1% dextran sulfate sodium (DSS) to their drinking water continuously for 8 weeks, and HLJD decoction at the doses of 2 and 4 g/kg was administered orally to mice daily from the second week until experimental endpoint. Stool consistency scores, blood stool scores, and body weights were recorded weekly. Disease activity index (DAI) was determined before necropsy, where colon tissues were collected for biochemical analyses. In addition, the fecal microbiome of treated mice was characterized using 16S rRNA amplicon sequencing. Results HLJD decoction at doses of 2 and 4 g/kg relieved DSS-induced chronic colitis in mice by suppressing inflammation through compromised macrophage activity in colonic tissues associated with the colony-stimulating factor 1 receptor (Csf1r)/Src pathway. Furthermore, the HLJD formula could modify the gut microbiota profile by decreasing the abundance of Bacteroides, Odoribacter, Clostridium_sensu_stricto_1, and Parasutterella. In addition, close correlations between DAI, colon length, spleen weight, and gut microbiota were identified. Discussion Our findings revealed that the HLJD formula attenuated DSS-induced chronic colitis by reducing inflammation via Csf1r/Src-mediated macrophage infiltration, as well as modulating the gut microbiota profile.